Gender differences in the incidence, characteristics and hospital admission outcomes of fall-related injuries in older adults in Victoria, Australia, over 5 years from 2018/19 to 2022/23 - Berecki-Gisolf, Janneke; Rezaei-Darzi, Ehsan; Natora, Aleksandra Helena (Frontiers in Public Health, 2024)
BackgroundFalls are the leading cause of injury morbidity and mortality in older adults. This study aimed to: (1) Explore gender differences in falls injury incidence and outcomes in Victoria, Australia; and (2) Test if these differences are explained by patient demographics and clinical complexity.MethodFall-related injury admissions records from 1-JULY-2018 to 30-JUNE-2023 were extracted from the Victorian Admitted Episodes Dataset. Admissions for injury (S00-T98) caused by a fall (W00-W19), in males and females aged 60+ years, were selected using ICD-10-AM codes. Incidence was calculated as annual falls admissions per 100,000 population. Gender differences in terms of demographics, falls details, injury types, complexity and admission outcomes were tested using logistic regression models.ResultsThere were 187,878 fall-related injury admissions: 67,635 (36.0%) by males and 120,243 (64.0%) by females. The incidence rate ratio peaked at 1.52 (female: male) at 70–79 years. Compared to males, female fall injuries were more likely due to same-level falls and to occur at home. Female sex was associated with fractures and male sex was associated with head injuries. Although female sex was associated with surgery and longer hospital stay, death-in-hospital was associated with male sex, with and without adjustment for patient demographics, fall details, injury type and clinical complexity.ConclusionThis contemporary gender-stratified study provides important evidence relevant to falls prevention and management. The findings suggest that same-level falls prevention is of particular relevance to females while in males, improved hospital outcomes and fall-related injury survivability, and any underlying frailty, should be prioritized.